TRAP OF CLASSROOM HOURS" AND A NEW MODEL OF EDUCATION - Evgeny V. Balatsky (Высшее образование в России)
The article describes the results of the implementation of the road map, produced by the Government of Russian Federation, concerning the increase of remuneration of academic staff of higher education institutions. It is shown that in 2016, the specified parameter was 123% compared to the planned 200% in 2017. The assessment of the necessary financial subsidies for access to the set standard is made in the article and it is argued that these subsidies are unrealistic for the current budget deficit. In this regard, it is concluded that the increase in the salaries of the teaching staff of the universities will be at the expense of their reduction, and this within the current model of education creates so-called trap of classroom hours, which does not to maintain the quality of education. To overcome this situation, it is proposed to introduce a new model of higher education, which combines traditional classroom system load and the system of distance education.